Investigating the Environmental Kuznets Curve Hypothesis in Egypt: The Role of Renewable Energy and Trade in Mitigating GHGs - El-Aasar, Khadiga Mohamed; Hanafy, Shaimaa A. (International Journal of Energy Economics and Policy, 2018)
This paper aims to investigate the existence of the environmental Kuznets curve (EKC) for Egypt during the period 1971âˆ’2012. Also, it attempts to examine the potential role of renewable energy and trade in mitigating greenhouse gas emissions in Egypt. Accordingly, the study examines the dynamic relationship between the GHG emissions, economic growth (real gross domestic product [GDP] per capita), renewable energy consumption (% of total), and trade openness. Using Autoregressive Distributed Lag bounds testing approach, the empirical evidence of the EKC hypothesis is analyzed. The main findings of the analysis, concerning the validity of EKC, reveal that the EKC hypothesis does not exist for GHG emissions in Egypt for both short - and long-term. In addition, the empirical results indicate the potential significant role of renewable energy to reduce GHG emissions. However, it has been found that trade openness has insignificant impact on GHG emissions. Keywords: Greenhouse Gas Emissions, Environmental Kuznets Curve, Renewable Energy, Egypt JEL Classifications: C32, O55, Q43, Q5